Green Synthesis of Bis(indolyl)methanes Catalysed by Salicylic Acid - Hoda Banari (Science Faculty of Chiang Mai University, 2019)
In this contribution, salicylic acid (SA) has been used to catalyze synthesis of a series of biologically relevant 3,3¢-bis(indolyl)methanes (BIMs) via the electrophilic substitution of indole derivatives on aldehyde compounds. The optimum catalyst loading was observed at 15 mol%. The procedure is simple and the expected bis-heterocyclic compounds were isolated in good to high yields. The present protocol provides the advantages of convenience, mild reaction conditions, eco-friendliness, energy-saving, and no use of hazardous solvents.